Exposed NEST.CO.LOGY - Chara Charisma El Miracle; Freddy Handoko Istanto; Maureen Nuradhi (Universitas Ciputra Surabaya, 2015)
Nowadays, people find restaurant or cafe not just for the food. But now restaurant or cafe become a place for recreation, meeting and leisure places. NEST.CO.LOGY will be one of recommended place to eat and get different dining experiences. NEST.CO.LOGY become the ambassador restaurant for NEST’co the bistro. Both of them are located in Semarang. NEST.CO.LOGY will bring a new concept with exposed design and molecular gastronomy. NEST.CO.LOGY exposing many detail. From the building form, interior design, service and this restaurant will exposing the process to make the food and beverage with modern technic culinary, molecular gastronomy.Molecular gastronomy is a technic that investigate physical and chemical transformation on food making process. The purpose is to make a different taste and texture of food.The design for this project will based on concept and style of Nest’co the bistro and based on molecular gastronomy character. This bistro use semi-industrial style. And molecular gastronomy have light color, transparent, and dynamic form.